Evolução do rifteamento e paleogeografia da margem Atlântica Equatorial do Brasil: Triássico ao Holoceno - Soares Júnior, Adilson Viana; Hasui, Yociteru [UNESP]; Costa, João Batista Sena; Machado, Fábio Braz (My University, 2011)
The Equatorial Atlantic Margin evolved from three rift systems recorded by a complex set of sedimentary basins developed since Upper Triassic to the Lower Cretaceous (Albian). The first rift system formed Foz do Amazonas Basin in Upper Triassic; the second phase formed Marajó Basin in Berriasian, a new rift in Foz do Amazonas Basin in Valanginian and Bragança-Viseu, Ilha Nova, São Luís e Barreirinhas basins in Aptian; the third phase formed Barreirinhas and Pará- Maranhão basins and a new rifting in the Foz do Amazonas Basin between the Aptian and Albian and evolved to continental break up. The main paleostress field during rift evolution was NE-SW and after the continental break up took the E-W direction, from the development of transform zones in the oceanic crust. From Miocene, South America was subjected to intraplate tectonics, which resulted in formation of E-W transcurrent faults that generated transtensive and transpressive segments that formed sedimentary basins and hills, resulting in changes in the drainage network. In Quaternary the landscape was modified by the last ice age that changed the sea level; the coastal drainage network was drowning resulting in the formation of the current line coast.

A Margem Atlântica Equatorial se formou a partir de três frentes distensivas, registradas por um complexo conjunto de bacias sedimentares desenvolvidas desde o Neotriássico até o Eocretáceo (Albiano). A primeira frente formou a Bacia da Foz do Amazonas no Neotriássico; a segunda frente formou a Bacia de Marajó no Berriasiano, uma nova fase rifte na Bacia da Foz do Amazonas no Valanginiano e as bacias de Bragança-Viseu, São Luís, Ilha Nova e Barreirinhas no Aptiano; a terceira fase envolveu as bacias de Barreirinhas, Pará-Maranhão e formou novo rifteamento na Bacia da Foz do Amazonas entre o Aptiano e o Albiano e evoluiu para fragmentação continental. O campo de paleotensão principal durante o rifteamento possuiu direção principal NE-SW e após a fragmentação continental assumiu direção próxima a E-W, com o desenvolvimento das zonas transformantes na crosta oceânica. A partir do Mioceno a placa Sul-Americana foi submetida à tectônica intraplaca, com formação de falhas transcorrentes E-W que geraram segmentos transtensivos e transpressivos que formaram bacias sedimentares e serras, com grandes modificações na rede de drenagem. No Quaternário, a paisagem foi modificada pelas glaciações e deglaciações que alteraram o nível do mar e impôs o afogamento da rede de drenagem, formando o litoral atual. Palavras-chave: Oceano Atlântico Equatorial, Oceano Atlântico Central, evolução de riftes mesozóicos, paleogeografia, Gondwana.
Rifting evolution and paleogeography of the Brazilian Equatorial Atlantic Margin: From Triassic to Holocene
Keywords: Central Atlantic Ocean; Equatorial Atlantic Ocean; Gondwana; Mesozoic rifting evolution; Paleogeography; Cretaceous; drainage network; Holocene; intraplate process; landscape structure; oceanic crust; paleogeography; paleostress; regional geology; rift zone; rifting; sedimentary basin; shelf break; stress field; tectonic evolution; Triassic; Atlantic Ocean; Atlantic Ocean (Central); Atlantic Ocean (Equatorial); Brazil; Foz do Amazonas Basin